From treaty-making to treaty-breaking : models for ASEAN external trade agreements - Kuijper, Pieter Jan; Mathis, James H.; Morris-Sharma, Natalie Y. (Cambridge [UK]: Cambridge University Press, 2015)
'This book comprising the ten member states of Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Viet Nam, has undertaken intensified integration into the ASEAN Community through the Rule of Law and Institutions in its 2007 Charter'--
Includes bibliographical references (pages 229-233) and index.
Keywords: Foreign trade regulation -- Southeast Asia; Rule of law -- Southeast Asia; Treaty-making power -- Southeast Asia; Southeast Asia -- Economic integration